Special Education Studies for Early Childhood in Several Countries - Ajeng Leksana Mulia; Herry Widyastono (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
This article discusses the comparison of early childhood special education in several countries such as South Korea, England, Japan, Malaysia and Indonesia. This article describes early childhood education programs especially for children with special needs. The article aims to explain the similarities and differences that exist in several countries regarding early childhood education. Each country has the same facilities and programs for children with special needs early by providing a learning conditional play program for children under 6 years.